Propuesta de automatización de la distribución eléctrica de la planta industrial Ingenio Monterrey Azucarera Lojana Compañía Anónima (MALCA), utilizando un sistema SCADA. - Santos Segarra, Patricio Yovanny (2013)
This research is based on automatic design system for the electrical distribution process, this proposal is focussed on solving the problematic that the industrial Monterrey Lojana Sugar limited Company (MALCA) is going through, as far as control transfers and electrical measurements is concerned, in order to get a better reading of these variables so we can have a good energy distribution within the plant. The main objective of this project is the design of the monitoring and control of the electricity distribution system in order to achieve a better energy transfer. This is achieved by identifying the optimal parameters for a good electrical distribution, and that way it can be possible to select the appropriate equipment to obtain a better quality in the process. The information provided by the electrical department lojano sugar factory was used, we also considered the features already installed in the distribution system in order to create an automatic control system that allows us to have the right conditions for the measurement of electrical parameters. For the realization of this investigative process we used an inductive method as well as the working technique based on the experience of workers in the electrical department of the operators of the plus Turbo - Generator, we also used the technique acquired during internship which gave us a guideline for the completion of the draft of the research project. Finally it was possible to define the control strategy and therefore sequential control algorithms. Besides with the implementation of the graphical interface we were able to obtain the energy distribution process in real time taking into consideration that this is a very economical and reliable system